2018
DOI: 10.1039/c8ra02924e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bioconversion of hydrogen and carbon dioxide to methane using a micro-nano sparger system: mass balance and energy consumption

Abstract: Simultaneous CO2 removal with renewable biofuel production can be achieved by methanogens through conversion of CO2 and H2 into CH4. However, the low gas–liquid mass transfer (kLa) of H2 limits the commercial application of this bioconversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In this way, a better distribution of gas bubbles with smaller sizes will favor mass transfer, thanks to the increase in the overall surface area, but also because of the higher time bubbles would spend inside the digester due to the lower buoyancy force and lower rising speed [133]. The experiences performed by Liu et al [134] demonstrated that introducing hydrogen in the form of nano-bubbles allowed for higher methane production rates than those obtained from micro-bubbles. However, the higher energy requirement to produce such small bubbles may eliminate any benefit associated with a higher methane production rate.…”
Section: Mass Transfer Limitationsmentioning
confidence: 99%
“…In this way, a better distribution of gas bubbles with smaller sizes will favor mass transfer, thanks to the increase in the overall surface area, but also because of the higher time bubbles would spend inside the digester due to the lower buoyancy force and lower rising speed [133]. The experiences performed by Liu et al [134] demonstrated that introducing hydrogen in the form of nano-bubbles allowed for higher methane production rates than those obtained from micro-bubbles. However, the higher energy requirement to produce such small bubbles may eliminate any benefit associated with a higher methane production rate.…”
Section: Mass Transfer Limitationsmentioning
confidence: 99%
“…was not changed after 10 days. The limit of the methane production rate (VVD) seems to be due to the low solubility of hydrogen and limitations of mass transfer, such as low mixing efficiency between cells in liquid (biocatalyst) and gas (substrate) in the BC [29,30]. VVD is dependent on the gas inflow rate, as shown in Equation (1).…”
Section: Methane Production In the St And Bcmentioning
confidence: 99%